Experiment in Architecture and Bauhaus-Weimar - Tatiana, Reshetnikova (Architecture Image Studies, 2020)
Experimentation as a method of design was announced in Bauhaus Weimar in the early twentieth century. In 1920, Gropius developed the concept of “Baukasten im großen” (Building Blocks at Large) – a building set of six elements in scale 1:1. Based on this principle, only one experimental building was realized – “Haus am Horn.” In the late 1990s, Bauhaus-University Weimar initiated the project “Neues Bauen am Horn” – an experiment of building Bauhaus style dwellings adapted to the new socio-economic situation.